PENGARUH MEDIA PEMBELAJARAN, EKSTRAKURIKULER, FASILITAS BELAJAR, PERHATIAN ORANG TUA TERHADAP MINAT BELAJAR PELAJARAN EKONOMI - Indah Permata Bunda; Erita Sofyan; Indra Mulia Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted with the aim of analyzing the extent of the influence of learning media, extracurricular activities, learning facilities, and parental attention on class The research used a quantitative approach with a population of all class X Phase E students totaling 93 people, and the sampling technique was carried out using total sampling. The data analysis process was carried out with the help of multiple linear regression using Eviews 12 software. The research results showed several important findings, namely: (1) learning media had a significant influence on students' interest in learning; (2) extracurricular activities make a significant contribution to increasing interest in learning; (3) adequate learning facilities have been proven to have a significant effect on interest in learning; (4) parental attention also has a significant influence on interest in learning; and (5) simultaneously, these four variables have a very significant effect on students' learning interest. Thus, increasing interest in learning can be realized through optimizing learning media, developing extracurricular activities, providing supportive learning facilities, and continued attention from parents.